The Uses and Gratifications Theory, Subjective Norm, and Gender in Influencing Studentsâ Continuance Participation Intention in LinkedIn - Paftalika, Reiza Bani; Hananto, Arga (Bina Nusantara University, 2018)
This research investigated how subjective norm and motives from Uses and Gratifications Theory (UGT) affected continuance participation intention. In addition, this research examined the role of gender as a moderating variable in the relationship. A moderated regression analysis was conducted on a sample of 246 respondents selected by purposive sampling technique. The result indicates that subjective norm, all uses, and gratifications motives in the model (information seeking, self-discovery, maintaining interpersonal connectivity, social enhancement, and entertainment value) affect continuance participation intention of female students. For male students, information seeking does not significantly affect continuance participation intention. Subjective norm affects male students more strongly than female students. Then, information seeking affects female students more than male students. This research adds more insights into the literature on continuance participation intention, particularly on the role of gender.